Longitudinal evaluation of a teacher education course presented to dental faculty - Jedrychowski, J R; Galligani, D J (Journal of dental education, 1978)
A three-day course on teaching methods was held for dental educators who were at various stages of their careers. The course was presented by the staff of the Academic Instructor and Allied Officer School of the Department of the Air Force. The purpose of the course was to aid in acquiring new knowledge of teaching methods and to produce behavioral changes in the participants' teaching techniques. A longitudinal evaluation demonstrated that participants changed teaching behaviors related to the courses' goals, and acquired and retained a significant amount of factual information presented in the course.